Origem e distribuição do nervo isquiático em fetos de suínos (Sus scrofa domesticus - Linnaeus, 1758) da linhagen Dan Bred - Rezende, Paulo Antônio Moreira Santos Lemos (2016)
The objective was to study the origin and distribution of the sciatic nerve in pig fetuses (Sus scrofa domesticus - Linnaeus, 1758) lineage Dan Bred. 30 animals (15 males and 15 females) come from farms of the Mineiro Triangle region were used. Specimens were injected with aqueous solution of 10% formaldehyde and then dissected. The sciatic nerve originated in antimeres 83.32% of the ventral ramus of the fifth lumbar spinal nerve (L5) in 96.66% (L6), 6.66% (L7) in the branch 100.00% the first sacral ventral spinal nerve (S1) and 66.66% (S2). Nerve formation occurred in 50.00% of animals the L5 union, L6, S1 and S2; in 30.00% of L5, L6 and S1; 12.90% for L6, S1 and S2; 3.33% in L6, L7, L5 and S1, S1 and S2. In their path, said nerve sent branches to the deep gluteus muscles, medium, surface, accessory, semitendinosus, semimembranosus, biceps femoris, tensor can and square femoral fascia in all studied specimens, less frequently for the twin muscles. Significant differences in the number of sciatic nerve branches issued to muscles between the sides and between the sex of the animals were not observed.